1991
DOI: 10.1038/353815a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of insecticidal δ-endotoxin from Bacillus thuringiensis at 2.5 Å resolution

Abstract: The structure of the delta-endotoxin from Bacillus thuringiensis subsp. tenebrionis that is specifically toxic to Coleoptera insects (beetle toxin) has been determined at 2.5 A resolution. It comprises three domains which are, from the N- to C-termini, a seven-helix bundle, a three-sheet domain, and a beta sandwich. The core of the molecule encompassing all the domain interfaces is built from conserved sequence segments of the active delta-endotoxins. Therefore the structure represents the general fold of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
661
0
11

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(692 citation statements)
references
References 42 publications
20
661
0
11
Order By: Relevance
“…Most significantly, incorporation of Cry1Ab oligomers into cell membrane does not result in the formation of lytic pores and, therefore, argues against the 'pore-formation model' postulated previously. [22][23][24][25] In the pore-forming model of Cry toxin action, the toxin monomers are considered precursors to oligomeric assembly. 21,25 The formation of toxin oligomer also has been postulated to be the result of the interaction of monomers that were bound to the cadherin receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most significantly, incorporation of Cry1Ab oligomers into cell membrane does not result in the formation of lytic pores and, therefore, argues against the 'pore-formation model' postulated previously. [22][23][24][25] In the pore-forming model of Cry toxin action, the toxin monomers are considered precursors to oligomeric assembly. 21,25 The formation of toxin oligomer also has been postulated to be the result of the interaction of monomers that were bound to the cadherin receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, Cry toxin action was believed to involve the formation of lytic pores that are the result of assembly of toxin molecules as oligomers in membrane. [22][23][24][25] However, there is no definitive correlation between the association of Cry toxin oligomer complexes and toxic action. Studies of mutated Cry toxin proteins have shown that neither the toxin oligomer complex nor commensurate changes in membrane vesicle permeability correlate directly with toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The three dimensional structures of six Cry toxins with different insect specificities have been solved [2,3,9,15,22,26]. These toxins are composed of three domains -domain I, a seven α-helix bundle involved in membrane insertion, oligomer formation and pore formation [4]; domain II, a three anti-parallel β-sheets packed around a hydrophobic core in a "beta-prism" involved in receptor interaction [4]; and domain III, a β-sandwich of two antiparallel β-sheets also involved in receptor interaction [4].…”
Section: Bt Cry Toxinsmentioning
confidence: 99%
“…Further, an alternative to gene pyramiding would be to use synthetic genes of multiple efficacies. Cry proteins share a common three domain structure (Li et al 1991). In simple words, hybrid (Synthetic) toxins produced through inclusion of a domain from another toxin results in increased potency of the fused protein by the shift in receptor binding (Bosch et al 1994).…”
Section: Introductionmentioning
confidence: 99%